Assessment of dental fluorosis in schoolchildren using a community index (CFI) - V. V. Belyaev; O. A. Gavrilova; I. V. Belyaev; O. A. Myalo; S. V. Konovalov (Эндодонтия Today)
Aim. To assess the significance of dental fluorosis for public health using the CFI index.Materials and metods. Dental fluorosis was evaluated in 622 students of 12.15 years old according to the WHO methodology and CFI was calculated for four settlements of the Tver region.Results. The average prevalence of dental fluorosis was 36.5% with variability in the values of groups of schoolchildren from 5.2% to 66.7%. The significance of dental fluorosis for public health ranged from “negative” to “medium” (CFI 0.1–1.2) in the settlements of the region, from “insignificant” to “medium” (CFI 0.7–1.7) in city Tver.Conclusions. When planning measures to prevent dental fluorosis in children in the Tver region, it is recommended that CFI indicators be taken into account.